Introduction to a Special Issue: Social Europe: The Changing Contours of Transnational Employment Relations in the European Union - Erne, Roland; Hauptmeier, Marco; Pulignano, Valeria; Turnbull, Peter (Industrial & labor relations review, 2024)
Employment relations in Europe today differ from how they were prior to the 2008 financial crisis and the COVID-19 pandemic, as key terms and conditions (e.g., wages) and sectors of economic activity (e.g., platform work and the green economy) are now subject to direct political intervention by the European institutions. Transnational (horizontal) competition within the Single European Market has long provided a context for national employment relations in Europe, and various national institutions impacted workers’ rights and conditions of employment. Under the new economic governance (NEG) regime triggered by the financial crisis, political (vertical) intervention in employment relations created strong pressure toward the commodification of labor. The COVID pandemic involved policymaking in the opposite (decommodifying) direction. That said, and as the articles in this special issue clearly demonstrate, commodifying pressures are still strong, and the full realization of Social Europe is arguably as elusive as ever.